Gene expression analysis in recurrent benign paroxysmal positional vertigo: a preliminary study - Oh, Eun Hye; Lee, Jin-Ok; Kim, Hyun Sung; Park, Ji-Yun; Choi, Seo Young; Choi, Kwang-Dong; Kim, Ji-Soo; Choi, Jae-Hwan (Frontiers in Neurology, 2023)
Objectives This study aimed to determine the pathophysiology of recurrent benign paroxysmal positional vertigo (BPPV) in young patients using gene expression profiling combined with bioinformatics analysis. Methods Total RNA was extracted from the whole blood of four young patients with recurrent BPPV and four controls. The differentially expressed genes (DEGs) between the groups were screened using a microarray analysis based on the cutoff criteria of |log2 fold change| > 1 and an adjusted p-value of < 0.05. Functional enrichment analysis of DEGs was performed using Gene Ontology analysis, and the protein–protein interaction (PPI) network was constructed using the Search Tool for the Retrieval of the Interacting Genes database. Results A total of 39 DEGs were detected between the BPPV and control samples, comprising 33 upregulated DEGs and six downregulated DEGs in the BPPV group. Functional enrichment analysis indicated that the upregulated DEGs were significantly enriched in terms related to metabolic processes and the immune system. Two main pathways were extracted from the PPI network: one was associated with oxidative phosphorylation and stress and the other with the adaptive immune system and extracellular matrix degradation. Conclusion The findings of our bioinformatics analysis indicated that oxidative stress or extracellular matrix degradation due to immune-mediated inflammatory responses may contribute to the development of recurrent BPPV in young patients.